Persepsi Perawat Terhadap Implementasi Budaya Keselamatan Pasien Di Ruang Rawat Inap Terpadu Rumah Sakit H.Adam Malik Medan - Betty Sinaga; Mappeaty Nyorong; Nuraini Nuraini (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
Patient safety is a hospital service system that provides safer patient care. WHO (World Health Organization) publications report patient safety incidents that medical errors occur in 8% to 12% of inpatient rooms at H.Adam Malik Hospital Medan. Patient safety incidents that occur include nosocomial infections, patient falls, and medication errors. Each of these incidents exceeded the established standards. The purpose of this study was to evaluate nurses' perceptions of the implementation of patient safety culture at H.Adam Malik Hospital MedanThe research design used was qualitative research. The characteristics of the key informants are the head of the nursing field, the head of the room, the head of pharmacy, the nursing committee and the head of the Quality Improvement and Patient Safety (PMKP) section, while the main informants are nurses. Qualitative data collection techniques using the Triangulation method. Data analysis using qualitative descriptive with data source triangulation stagesThe results showed that patient identification, effective communication, drug safety and risk of infection had gone well, while site marking and the risk of falling patients had not gone well.The conclusion of this study is that patient identification, effective communication, drug safety and risk of infection have gone well, while site marking and the risk of patients falling have not gone well. It is hoped that this can be an illustration of the application of patient safety to improve the quality of health services through the achievement of hospital achievements so that it can be used as the basis for taking a further policy and increasing the satisfaction of each patient who comes.